Endoscopic treatment of fistula after sleeve gastrectomy: results of a multicenter retrospective study - Christophorou, Dimitri; Valats, Jean-Christophe; Funakoshi, Natalie; Duflos, Claire; Picot, Marie-Chistine; Vedrenne, Bruno; Prat, Frédéric; Bulois, Phillipe; Branche, Julien; Decoster, Sébastien; Coron, Emmanuel; Charachon, Antoine; De Chambrun, Guillaume Pineton; Nocca, David; Bauret, Paul; Blanc, Pierre (Endoscopy, 2015)
Background and study aims: Fistula is the main complication of laparoscopic sleeve gastrectomy (LSG), for which healing is difficult to achieve. The aims of the study were to evaluate the efficacy of interventional endoscopy for post-LSG fistula treatment, to evaluate various endoscopic techniques used and identify their complications, and to identify predictive factors of healing following endoscopic treatment. Patients and methods: This retrospective multicenter study included patients with post-LSG fistula. Therapeutic procedures were evaluated, taking into account complications and healing times. Endoscopic procedures were considered to have promoted healing if no other surgical procedure was performed. Predictive factors of healing were identified by univariate and multivariate analysis. Results: A total of 110 patients were included, of whom 6 (5.5 %) healed spontaneously, 81 (73.6 %) healed following endoscopic treatment, and 19 (17.3 %) healed following surgery. Healing rates following endoscopic treatment were 84.4 % in the first 6 months of treatment (65/77), 52.4 % for treatment lasting 6 – 12 months (11/21), and 41.7 % after 12 months of treatment (5/12). A drainage procedure (surgical, endoscopic, or percutaneous) was performed in 92 patients (83.6 %). A total of 177 esogastric stents were placed in 88 patients (80.0 %). Surgical debridement, clip placement, glue sealing, and plug placement were also performed. Multivariate analysis identified four predictive factors of healing following endoscopic treatment: interval < 21 days between fistula diagnosis and first endoscopy (P = 0.003), small fistula (P = 0.01), interval between LSG and fistula ≤ 3 days (P = 0.01), no history of gastric banding (P = 0.04).Conclusion: Endoscopic treatment facilitated healing of post-LSG fistula in 74 % of patients. Early endoscopic treatment increased the likelihood of success, and was most effective during the first 6 months of management. After this point, surgical treatment should be considered.